Gender differences in thyroid system function: relevance to bipolar disorder and its treatment. (19th November 2013) - Bauer, Michael; Glenn, Tasha; Pilhatsch, Maximilian; Pfennig, Andrea; Whybrow, Peter C
<x xml:space="preserve">Abstract</x> Objectives Thyroid hormones play a critical role in the functioning of the adult brain, and thyroid diseases impair both mood and cognition. This paper reviews gender differences in thyroid system function that are relevant to the diagnosis and treatment of bipolar disorder. Methods The study comprised a comprehensive literature review of gender differences in thyroid disease that are pertinent to mood disorders. Results The prevalence of thyroid disease was found to be much higher in females than males, and to increase with age. The most commonly detected abnormality was subclinical hypothyroidism, which was found to occur in up to 20% of postmenopausal women. Females also had higher rates of thyroid autoimmunity. Individuals at risk for thyroid disease, such as adult females, may have had less ability to compensate for additional challenges to thyroid metabolism, including lithium treatment. Thyroid abnormalities were associated with a poorer response to standard treatments for mood disorders. Females with treatment‐resistant mood disorders may have responded better than males to adjunctive therapy with thyroid hormones. Conclusions Disturbances of thyroid system function, which occur commonly in females, may complicate the diagnosis and treatment of mood disorders. In particular, this is clinically relevant during lithium treatment because lithium may impair vital thyroid metabolic pathways secondary to its anti‐thyroid activity.